Prevalence and impact of the use of electronic gadgets on the health of children in secondary schools in Bangladesh: A cross‐sectional study. Issue 4 (1st October 2021) - Rashid, S M Mahbubur; Mawah, Jannatul; Banik, Ema; Akter, Yasmin; Deen, Jobaier Ibne; Jahan, Amina; Khan, Navid Mahmood; Rahman, Md. Mofijur; Lipi, Nasrin; Akter, Farhana; Paul, Alak; Mannan, Adnan
Abstract: Background and Aims: Use of technological gadgets has rapidly been increasing among adolescents, which may result in health issues and technology addiction. This study focuses on the prevalence of usage of technological gadgets and health‐related complications among secondary school‐going children of Bangladesh. Methods: A total of 1803 secondary school students from 21 different districts of Bangladesh participated in the study. The children were asked questions relating to their access to electronic gadgets, time spent on outdoor activities, and whether they experienced any health‐complications as an after‐effect of the usage. A binary logistic regression model was adapted considering time spent on gadgets as an independent variable and health problems (physical and mental) as the dependent variable. Results: Among all the gadgets, 67.11% of the participants were reported to use mobile phones on a daily basis. Due to the ongoing COVID‐19 pandemic, 24.48% of respondents used electronic gadgets for attending online classes. The participants were reported to use gadgets significantly more ( P  < .05) in 2020 as compared to 2019. Children showed less tendency to spend time in outdoor activities. More than 50% of the participants spend time doing outdoor activities for less than 1 hour daily. An association between gadget use and health problems like headache, backache, visual disturbance, and sleeping disturbance has been observed in our study. Conclusion: This study demonstrates that different socio‐demographic factors have influence on the use of gadgets by children, and this use has greatly been affecting both the physical and mental health of the secondary school‐going students of Bangladesh.